A Sleight of Mind: The Idea of Magic and the Narrative Structure of A Christmas Carol by Charles Dickens - Nizar Zouidi (Zagadnienia Rodzajów Literackich)
The nineteenth century was an age of reason and industrialization. Magic and mythical creatures ceased to exist for the rational minds of the time. Yet, despite the intellectual hostility to magic and mysticism, their sway over popular culture and the literary world remained undisturbed. Magic even found other ways to return. One of these is stage magic. In the 1840s, the stage magician John Henry Anderson dazzled the audiences in London with his performances so much so that Sir Walter Scott called him the Great Wizard of the North (referring to his Scottish origins). In A Christmas Carol, Dickens adds vivacity to his narrative through the use of narrative theatrics that can be described as pertaining to stage magic. In the novella, a ludicrous form of white magic transforms the main character. The other characters are baffled by the inexplicable change in his behaviors. The transformation seems magical even to them. While hidden from their eyes, Scrooge receives four strange night visitors who reform him through a series of visions. When he finally returns to the “real” world, Scrooge is a different person. What takes place in the novella can in many respects be compared to the tricks used in stage magic (where an item is hidden from the sight of the spectators only to reappear in a different form). The use of magic in the novella, therefore, goes beyond the story. Indeed, a “magical” sleight of mind structures the very narrative of A Christmas Carol. This paper seeks to trace the influence of the idea of magic on the narrative structure and techniques of Dickens’ novella. It argues that, in many respects, the narrator can be described as a magician performing tricks on characters and readers alike.